Tijdens een vergadering over sociale wetgeving. V.l.n.r. : Dales, Van der Doef, Wöltgens, Kombrink - Naeff, Nico
Tijdens een vergadering over sociale wetgeving. V.l.n.r. : Dales, Van der Doef, Wöltgens, Kombrink.